New perspectives on Eastern Baltic cod movement patterns from historical and contemporary tagging data - Mion, Monica; Griffiths, Christopher A.; Bartolino, Valerio; Haase, Stefanie; Hilvarsson, Annelie; Hüssy, Karin; Krüger-Johnsen, Maria; Krumme, Uwe; Carlstedt Lundgreen, Regitze Benedicte; Lövgren, Johan; McQueen, Kate; Plikshs, Maris; et al. (Marine Ecology Progress Series, 2022)
Knowledge of the movement patterns and area utilisation of commercially important fish stocks is critical to management. The Eastern Baltic cod Gadus morhua, one of the most commercially and ecologically important stocks in the Baltic Sea, is currently one of the most severely impacted fish stocks in Europe. During the last 2 decades, this stock has experienced drastic decreases in population size, distributional range, individual growth and body condition, all of which may have affected the movements between different areas of the Baltic Sea. In this study, we investigated the seasonal movement patterns of Eastern Baltic cod by re-analysing historical tagging data collected by the countries surrounding the Baltic Sea (1955-1988) and compared historical patterns with contemporary data from a recent international tagging experiment (2016-2019). Our re-analyses of historical data showed the presence of different movement behaviours, i.e. resident or seasonally migratory, with larger distances moved by cod released in the northern and central Baltic areas compared to cod released in the southern Baltic areas. Furthermore, trends from the recent tagging experiment indicate a persistent resident strategy in the southern Baltic area. These findings present additional information on general movement patterns and area utilisation of Eastern Baltic cod that could inform future management actions and aid stock recovery.